Small intestinal bacterial overgrowth in chronic liver disease: an updated systematic review and meta-analysis of case-control studiesResearch in context - Ayesha Shah; Liam Spannenburg; Parag Thite; Mark Morrison; Thomas Fairlie; Natasha Koloski; Purna C. Kashyap; Mark Pimentel; Ali Rezaie; Gregory J. Gores; Michael P. Jones; Gerald Holtmann (EClinicalMedicine)
Summary: Background: Small Intestinal Bacterial Overgrowth (SIBO) has been implicated in the pathophysiology of chronic liver disease (CLD). We conducted a systematic review and meta-analysis to assess and compare the prevalence of SIBO among CLD patients (with and without with complications of end stage liver disease) and healthy controls. Methods: Electronic databases were searched from inception up to July-2024 for case–control studies reporting SIBO in CLD. Prevalence rates, odds ratios (ORs), and 95% confidence intervals (CIs) of SIBO in patients with CLD and controls were calculated utilizing a random-effects model. The protocol was prospectively registered with PROSPERO (CRD42022379578). Findings: The final dataset included 34 case–control studies with 2130 CLD patients and 1222 controls. Overall, the odds for SIBO prevalence in CLD patients compared to controls was 6.7 (95% CI 4.6–9.7, p < 0.001). Although the prevalence of SIBO among patients with CLD with cirrhosis was higher at 42.9% (95% CI: 35.9–50.2) compared to 36.9% (95% CI: 27.4–47.6) in those without cirrhosis, this difference failed statistical significance. However, CLD patients with decompensated cirrhosis had a significantly higher prevalence of SIBO compared to those with compensated cirrhosis, with an OR of 2.6 (95% CI: 1.5–4.5, p < 0.001). Additionally, the prevalence of SIBO was significantly higher in CLD patients with portal hypertension (PHT) than in those without PHT, with an OR of 2.1 (95% CI: 1.4–3.1, p < 0.001). The highest prevalence of SIBO was observed in patients with spontaneous bacterial peritonitis (SBP) (57.7%, 95% CI 38.8–74.5), followed by patients with hepatic encephalopathy (41.0%, 95% CI 16.0–72.3) and patients with variceal bleed (39.5%, 95% CI 12.1–75.6). Interpretation: Overall, there is a significantly increased prevalence of SIBO in CLD patients compared to controls. The prevalence is even higher in CLD patients with PHT, especially those with SBP. This meta-analysis suggests that SIBO is associated with complications of CLD and potentially linked to the progression of CLD. Funding: National Health and Medical Research Council, Centre for Research Excellence (APP170993).